1991
DOI: 10.1002/ana.410300210
|View full text |Cite
|
Sign up to set email alerts
|

Reduced D2 dopamine and muscarinic cholinergic receptor densities in caudate specimens from fluctuating parkinsonian patients

Abstract: Binding of spiperone and 3-quinuclidinyl benzilate (QNB), both labeled with hydrogen 3 (3H), were measured in caudate tissue obtained from 8 living parkinsonian patients at the time of cerebral transplantation. This was clinically homogeneous group of patients. All remained predominantly responsive to levodopa, although with marked disability secondary to clinical fluctuations (short-duration responses) and medication-induced dyskinesias; all were receiving substantial doses of levodopa and 6 of the 8 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Availability of endogenous dopamine and dopamine receptor density decline with increasing age (Marksman et al, 1979;Cot6 and Kremzner, 1983;De Keyser et al, 1990;Martin et al, 1989) and the combined age-and disease-related changes in the dopaminergic neurotransmission might insufficiently be compensated by dopaminergic therapy (Lloyd and Hornykiewicz, 1970;Lloyd et al, 1975;Melamed et al, 1981;Leenders et al, 1986;Hornykiewicz and Kish, 1986;Ahlskog et al, 1991;Brooks et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…Availability of endogenous dopamine and dopamine receptor density decline with increasing age (Marksman et al, 1979;Cot6 and Kremzner, 1983;De Keyser et al, 1990;Martin et al, 1989) and the combined age-and disease-related changes in the dopaminergic neurotransmission might insufficiently be compensated by dopaminergic therapy (Lloyd and Hornykiewicz, 1970;Lloyd et al, 1975;Melamed et al, 1981;Leenders et al, 1986;Hornykiewicz and Kish, 1986;Ahlskog et al, 1991;Brooks et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, parkin deficiency was associated with marked elevation of both D 1 and D 2 receptors. Indeed, previous studies reported that although striatal D 2 binding increased in untreated patients with PD, adaptive postsynaptic mechanisms and treatment decreased this as the condition advanced (Ahlskog et al,1991; Brooks et al,1992; Ichise et al,1999). In a study of AR‐JP patients, Scherfler et al (2004) reported a global decrease in D 2 receptor and argued for parkin genetic defect itself or susceptibility to receptor downregulation after long‐term exposure to dopaminergic agents.…”
Section: Discussionmentioning
confidence: 98%
“…[39][40][41][42] The same, however, does not appear to be the case in the striatum of levodopa-treated patients in which either normal or decreased dopamine receptor binding/density has been reported. [41][42][43][44][45] Furthermore, in a recent PET study of levodopa-treated patients with PD with and without dyskinesias, no differences in D1 and D2 receptor binding between the two groups were observed. 42 In recent years, the role of nondopaminergic pathways in the pathogenesis of MRCs has received increasing investigative attention.…”
Section: What Notmentioning
confidence: 99%